2005
DOI: 10.1016/j.jacc.2004.10.053
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of hydroxyfasudil, a specific Rho-kinase inhibitor, on ischemia/reperfusion injury in canine coronary microcirculation in vivo

Abstract: Hydroxyfasudil exerts cardioprotective effects on coronary I/R injury in vivo, in which NO-mediated mechanism may be involved through preservation of eNOS expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 43 publications
2
36
0
1
Order By: Relevance
“…However, the regulation of coronary vascular tone may be mediated, not only by NO, but also by the endothelium derived hyperpolarizing factor (EDHF) and adenosine (24). Yada et al have demonstrated that endogeneous H 2 O 2 , an EDHF, and rhokinase inhibition mediated coronary vasodilation to a greater extent in arterioles than in small arteries (7,8,24). In the present study, preservation of endotheliumdependent vasodilation by edaravone was noted to a greater extent in the small arteries (Fig.…”
Section: Edaravone Preserves Nitric Oxide and Enossupporting
confidence: 53%
See 1 more Smart Citation
“…However, the regulation of coronary vascular tone may be mediated, not only by NO, but also by the endothelium derived hyperpolarizing factor (EDHF) and adenosine (24). Yada et al have demonstrated that endogeneous H 2 O 2 , an EDHF, and rhokinase inhibition mediated coronary vasodilation to a greater extent in arterioles than in small arteries (7,8,24). In the present study, preservation of endotheliumdependent vasodilation by edaravone was noted to a greater extent in the small arteries (Fig.…”
Section: Edaravone Preserves Nitric Oxide and Enossupporting
confidence: 53%
“…4). Previous studies from our institution have also demonstrated a decrease in eNOS protein expression in ischemic myocardium following I / R (7,8). An in vitro study in HUVEC has shown that edaravone may increase eNOS expression via the inhibition of LDL oxidation (25).…”
Section: Edaravone Preserves Nitric Oxide and Enosmentioning
confidence: 69%
“…Another ROCK inhibitor, fasudil, also decreased myocardial infarct size in rats and this cardioprotective effect was blocked by cotreatment with phosphatidylimositol 3-kinase inhibitors or the NOS inhibitor, L-NAME [90]. Similarly, hydroxyfasudil reduced myocardial infarct size in dogs after ischemiareperfusion injury, with an improved vasodilator response via preservation of the eNOS expression [98]. Moreover, treatment with fasudil improved LV remodeling and inhibited the inflammatory response in mice irrespective of infarction size or time of treatment [97].…”
Section: Rock In Heart Diseasesmentioning
confidence: 93%
“…Yada et al [19] reported that hydroxyfasudil caused significant coronary vasodilation of both small arteries and arterioles in a dose-dependent manner. In the present study, the CBF did not increase after administration of fasudil at a clinically relevant dose.…”
Section: Discussionmentioning
confidence: 99%